Heat Transfer Analysis of 2D Steady Laminar Mixed Convection CNTs Blood base Nanofluid Flow over a Stretching Surface: Analytical Simulation - Ali Rehman; Ma Chau Khun; Dolat Khan; Arshad Jan (Journal of Applied and Computational Mechanics, 2025)
With the significant advancements in nanofluids, the fields of fluid dynamics and thermal management have experienced further development. Due to their enhanced thermal properties and capacity for customization to specific applications, nanofluids present a viable option for improving the efficacy and efficiency of various technological and industrial processes. The objective of this research article is to investigate the heat transfer properties of a blood-based steady laminar mixed convection flow of nanofluid over perpendicular stretched sheets. The non-Newtonian nanofluid's unique thermal properties, attributable to carbon nanotubes (CNTs), render it a suitable medium for enhancing heat transfer in biomedical applications. The flow model equations, one for momentum and another for energy, are transformed into a set of nonlinear ordinary differential equations through the application of appropriate similarity transformations. The governing nonlinear equations are solved semi-numerically using the Homotopy Analysis Method. This method is effective for obtaining series solutions to highly nonlinear differential equations. The Homotopy Analysis Method, developed by Shijun Liao in the 1990s, has applications in numerous disciplines of science and engineering. Several significant factors, including Local Grashof number, couple stress parameter, nanoparticle volume fraction, thermal radiation parameter, temperature exponent, and Prandtl number, are investigated, and their impact on the temperature and velocity profiles is examined. The study also considers the Nusselt number and skin friction coefficient. The results demonstrate that the addition of CNTs significantly increases heat transfer efficiency, thereby enhancing cooling in biological domains. This study contributes to our understanding of heat transfer enhancement in blood-based nanofluids with carbon nanotubes and provides important new insights for the development and improvement of thermal control systems in biomedical engineering. Furthermore, the findings of this study may inform the development of novel strategies to improve the efficacy of heat exchangers and cooling devices in medical applications.